1983
DOI: 10.1351/pac198855020289
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectra of acenes. Electronic structure and substituent effects

Abstract: The valence-electronic structure of the first three members of the acene series, benzene, naphthalene and anthracene, seems to be confirmed now by their photoelectron (PE) spectra. This especially holds for the r-ionizations which, according to their specific behaviour, can be assigned to different ionization modes. The vibrational fine structure of the observed systems is discussed. The effects of a series of substituents on the electronic structure of the parent molecules were traced in their PE spectra and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
54
1
2

Year Published

1984
1984
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(76 citation statements)
references
References 11 publications
19
54
1
2
Order By: Relevance
“…1 for 9-acetoxy, 9-bromo, and 9,lO-dibromoanthracene. The reliability in the values of El and that of the second ionization energy E2 listed in Table 1 was established by a comparison with those obtained independently by Klasinc and co-workers (10). The trend, as reported earlier, is for both El and E2 to generally increase with values of the Hammett a constant -that is, the presence of electron-attracting substituents leads to the stabilization of the HOMO as well as the SHOMO.…”
Section: Photoelectron Spectra Of Anthracene and Its Derivativessupporting
confidence: 55%
See 2 more Smart Citations
“…1 for 9-acetoxy, 9-bromo, and 9,lO-dibromoanthracene. The reliability in the values of El and that of the second ionization energy E2 listed in Table 1 was established by a comparison with those obtained independently by Klasinc and co-workers (10). The trend, as reported earlier, is for both El and E2 to generally increase with values of the Hammett a constant -that is, the presence of electron-attracting substituents leads to the stabilization of the HOMO as well as the SHOMO.…”
Section: Photoelectron Spectra Of Anthracene and Its Derivativessupporting
confidence: 55%
“…The comparison of the He(1) and He(I1) photoelectron spectra of anthracene with those of benzene and naphthalene has established the first ionization El at 7.43 eV to occur from a T-orbital (HOMO according to Koopmans' theorem) of b2, symmetry with maximum electron density at the 9-and 10-positions (10). The second ionization E2 at 8.53 eV occurs from the subjacent T-orbital (SHOMO) of big symmetry with a node at the 9-and 10-positions.…”
Section: Photoelectron Spectra Of Anthracene and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent literature data have shown that the CT band energies arising from interactions between different aromatic compounds (donors) and the tropylium cation (acceptor) follow a linear relationship with the IP of the aromatics (20). Figure 2 shows the same dependence of the transition energies of the CT bands in the diarylideneacetones on the IP of the aromatic compounds (21). This experiment indicates that the aryl groups are indeed the donors, and the (CHCH)*CO group is the acceptor moiety of the CT interactions.…”
mentioning
confidence: 63%
“…Naphthalene is composed of two fused benzenes, and it has been studied frequently with its derivatives for about fifty years, since 1968 (Yencha & El-Sayed, 1968;Kitagawa, 1968;Kaim, Tesmann & Bock, 1980;Klasinc, Kovac & Gusten, 1983;Meylan & Howard, 1991;Heinis, Chowdhury & Kebarle, 1993;Schiedt, Knott, Barbu, Schlag & Weinkauf, 2000;Lardin, Squires & Wenthold, 2001;Song, et al 2002). Ghiasi (Ghiasi, 2005) worked on the aromaticity of mono-and di-silanaphthalene after the first achievement of the synthesis of 1-Silanaphthalene was published by Takeda et al (Takeda, Shinohara & Tokitoh, 2002).…”
Section: Introductionmentioning
confidence: 99%